Inclusive education in health: the nurse as reader of educational technology for visually impaired - José Wicto Pereira Borges; Ana Célia Caetano de Souza; Thereza Maria Magalhães Moreira; Aline Maria Oliveira Loureiro; Anaíze Viana Bezerra de Menezes (Universidad de Alicante, 2017)
The objective was to report the case of inclusion of a visually impaired in health education activities with the nurse as lector of an educational technology. It is a case study carried out in Fortaleza, Ceará, Brazil. The research was carried out from the theory of Virginia Henderson. He was diagnosed Deficit knowledge. They applied to the scales of NOC "knowledge - disease control and disease process" to evaluate the results. Nursing interventions were performed through an Educational Technology: flipchart on hypertension, treatment adherence and quality of life. The album dealt six activities of the NIC taxonomy. For the implementation of nursing intervention was developed a method with the following steps: general description of the figure, detailing the figures and focus on the main message represented. The nursing results showed that the process of education in inclusive health occurred. In terms of measurement, the NOC scales have demonstrated acquisition of knowledge about complications of hypertension.